Salted egg white derived-peptides VF-4 and DR-8 improve DSS-induced colitis in mice by inhibiting NF-κB/MAPK/PI3K-AKT signaling pathways and modulating gut microbiota composition - Na Zhou; Na Wu; Yao Yao; Shuping Chen; Mingsheng Xu; Zhongping Yin; Yan Zhao; Yonggang Tu (Food Science and Human Wellness)
Inflammation underlies many chronic diseases, and inflammatory bowel disease (IBD) is a condition characterized by long-term inflammation of the gut. Egg whites have been shown to contain many beneficial active substances. Therefore, we obtained 2 peptides from salted egg white: Val-Val-His-Phe (VF-4) and Asp-Thr-Gln-Ala-Met-Pro-Phe-Arg (DR-8). The sodium dextran sulfate (DSS)-induced mice colitis model was used to evaluate its regulatory effect on colitis in vivo. The results showed that VF-4 and DR-8 improved the clinical symptoms of DSS-induced colitis, attenuated colon tissue damage, inhibited the activation of nuclear factor kappa-B (NF-‍κB)/mitogen-activated protein kinase (MAPK)/phosphoinositide 3-kinase-Akt (PI3K-AKT) signaling pathways, and inhibited the expression of inflammatory cytokines. 16S rRNA gene sequencing showed that VF-4 and DR-8 administration increased the relative abundance of intestinal beneficial bacteria including Lactobacillus, Blautia, and down-regulated the relative abundance of inflammation-related bacteria including Acinetobacter, Lachnospiraceae_NK4A136_group, Klebsiella. Moreover, the degree of correlation between pro-inflammatory cytokines and microbiota was as follows: interleukin-6 (IL-6) > tumor necrosis factor-α (TNF-α) > interleukin-1β (IL-1β) > interferon-γ (IFN-γ). In conclusion, this study suggests that salted egg white peptides VF-4 and DR-8 have a significant anti-inflammatory effect in vivo. It also provides a strategy for the treatment of IBD and a new way for the high-value utilization of salted egg white.